IBM Pelatihan Kader Dalam Deteksi Dini Lansia Dengan Demensia Di Desa Deliksari Gunungpati - Novita Wulan Sari; Margiyati Margiyati; Seftian Hidayati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
STIKES Kesdam IV/Diponegoro as one of the health universities has great potential in the form of human resources (HR) to play a role in the development of the target area in the health sector. The results of an interview with the Head of the Sekaran Community Health Center revealed that of the 5 sub-districts managed by the Sekaran Community Health Center, Sukorejo Sub-District is an area that has complex health problems. Health problems related to the elderly need attention that is no less important. The health of the elderly under the management of the elderly posyandu in the Sukerejo Deliksari sub-district area has been going well. It's just that this area related to handling the cognitive health problems of the elderly still needs more attention. One of the cognitive function disorders in the elderly is dementia. There is no health care related to dementia in this area, this is because elderly posyandu cadres consider the problem of dementia or senile dementia to be natural and normal for the elderly. So promotive and preventive efforts are needed by holding community service related to cadre training in early detection of elderly people with dementia health problems.